Намисто могильника Червоний Маяк (розкопки 2011—2013 рр.) - Дзнеладзе, О.С. (Археологія, 2016)
Статтю присвячено аналізу намиста з пізньоскіфського некрополя Червоний Маяк на Нижньому Дніпрі, який досліджувався Пізньоскіфською археологічною експедицією ІА НАН України у 2011—2013 рр. за участю автора. Розглянуто можливість використання намиста як хроноіндикатора. The research at Chervonyi Mayak cemetery was restarted in 2011 by the Late Scythian Archaeological Expedition of the Institute of Archaeology, NAS of Ukraine, led by O.V. Symonenko and with participation of the author. In 2011—2013, the expedition studied twelve graves. Most of the burials studied contained beads: monochrome and polychrome glass beads, beads with metal lining, and beads made of semiprecious stones, metal, amber, jet, as well as of Egyptian faience. The correlation of beads with other elements of clothing, especially fibulae and buckles, demonstrates that the beads of various types could be used as chronological marker. Mass findings of monochrome glass beads in graves rarely allow obtaining a narrow date and more often date a burial within the period of one or two centuries. The date of an assemblage can be specified owing to polychrome beads with compound decoration, the Egyptian faience beads, and items of semiprecious stones and figured pendants. The author used the typological scheme of Ye.M. Alekseyeva. Most types of the beads under study were in use from the 1 st century to the first half of the 2nd century AD and permit to date the graves where they have been found to this time. The beads of similar types were found in several graves at Chervonyi Mayak cemetery excavated by E.O. Symonovych and O.A. Gei, as well as at Zolota Balka cemetery. Despite the fact that the beads couldn’t be dated exactly, it is possible to use them for dating when there are no other chronology markers. Beads are often the only objects for the dating of a destructed grave. Исследования могильника Красный Маяк были возобновлены в 2011 г. Позднескифской археологической экспедицией ИА НАН Украины под руководством А.В. Симоненко и при участии автора. За 2011—2013 гг. экспедиция исследовала 12 погребений. В большинстве исследованных погребений найдены бусы — стеклянные монохромные и полихромные, с металлической прокладкой, из полудрагоценного камня, металлические, янтарные и гагатовые, а также бусины и бисер из египетского фаянса. Корреляция бус с другими элементами убора, в особенности с фибулами и пряжками, доказывает возможность использования бусин различных типов в качестве хроноиндикатора. Массовые находки монохромных стеклянных бус в могилах редко позволяют получить узкую дату, и чаще всего датируют погребение в диапазоне одного-двух веков. Точнее определить дату комплекса можно благодаря полихромным бусинам со сложным орнаментом, египетскому фаянсу, изделиям из полудрагоценных камней и фигурным подвескам. Типология бус дана по Е.М. Алексеевой. Большинство типов проанализированных бус бытовали в І — первой половине ІІ в. н. э., что позволяет отнести погребения, из которых они происходят, к этому времени. Аналогичные бусы были найдены в нескольких могилах Красного Маяка при раскопках Э.А. Сымоновича и О.А. Гей, а также в Золотобалковском могильнике. Несмотря на то, что бусы не дают дробной хронологии, их использование возможно для датирования погребений при отсутствии других хроноиндикаторов. Часто лишь благодаря бусам возможно получить дату разрушенной могилы.